A Data-Driven Investigation of Gray Matter–Function Correlations in Schizophrenia during a Working Memory Task - Michael, Andrew; King, Margaret D.; Ehrlich, Stefan; Pearlson, Godfrey; White, Tonya; Holt, Daphne J.; Andreasen, Nancy; Sakoglu, Unal; Ho, Beng-Choon; Schulz, S. Charles; Calhoun, Vince D. (Frontiers in Human Neuroscience, 2011)
The brain is a vastly interconnected organ and methods are needed to investigate its long range structure(S)–function(F) associations to better understand disorders such as Schizophrenia that are hypothesized to be due to distributed disconnected brain regions. In previous work we introduced a methodology to reduce the whole brain S–F correlations to a histogram and here we reduce the correlations to brain clusters. The application of our approach to sMRI (gray matter concentration maps) and fMRI data (GLM activation maps during Encode and Probe epochs of a working memory task) from patients with schizophrenia (SZ, n=100) and healthy controls (HC, n=100) presented the following results. In HC the whole brain correlation histograms for gray matter(GM)–Encode and GM–Probe overlap for Low and Medium loads and at High the histograms separate, but in SZ the histograms do not overlap for any of the load levels and Medium load shows the maximum difference. We computed GM–F differential correlation clusters using activation for Probe Medium, and they included regions in the left and right superior temporal gyri, anterior cingulate, cuneus, middle temporal gyrus and the cerebellum. Inter-cluster GM–Probe correlations for Medium load were positive in HC but negative in SZ. Within group inter-cluster GM–Encode and GM–Probe correlation comparisons show no differences in HC but in SZ differences are evident in the same clusters where HC versus SZ differences occurred for Probe Medium, indicating that the S–F integrity during Probe is aberrant in SZ. Through a data-driven whole brain analysis approach we find novel brain clusters and show how the S–F differential correlation changes during Probe and Encode at three memory load levels. Structural and functional anomalies have been extensively reported in schizophrenia and here we provide evidences to suggest that evaluating S–F associations can provide important additional information.